A revision of taxonomic relation between Oenothera perangusta and O. ersteinensis (Onagraceae) based on morphometric research and statistical analyses - Woźniak-Chodacka, Monika (Phytotaxa, 2018)
The taxonomic status of Oenothera ersteinensis and O. perangusta (sect. Oenothera, subsect. Oenothera; Onagraceae) has remained unresolved. According to the representatives of the so-called American school of taxonomy both names should be assigned, as their synonyms, to two separate, widely treated species (O. biennis and O. oakesiana, respectively) whereas  European researchers consider both taxa as very similar or even as a single species. In order to establish the taxonomic relation between these taxa, detailed morphometric research and statistical analyses—principal component analysis, correspondence analysis, discriminant analysis and Wald-Wolfowitz runs test—were performed. As a background to present the differentiation between the considered taxa, analyses of European representatives of two distinct and widely distributed species, O. biennis and O. oakesiana, were also conducted. The results revealed that the highest discriminatory power have mostly qualitative features. Oenothera ersteinensis turned out to be a distinct and well-separated species belonging to the series Oenothera whereas O. perangusta is most probably only a synonym name of O. oakesiana. Moreover, it was demonstrated that all the investigated specimens labelled as O. perangusta were in fact misrecognized representatives of O. ersteinensis. The updated map of distribution of O. ersteinensis is also provided.